Effect of cutting parameters on surface integrity in groove milling of Hastelloy-C276 using coated carbide end mills under dry and wet conditions - Abdulradha Al-Falahi, Muath Dheaa (2015)
The development of novel materials (superalloys) is an evolving process towards improving the serviceability of their components in hostile industrial environments. Hastelloy-C276 is one variation of nickel-based superalloys which is a ductile corrosionresistant superalloy that is widely used in chemical and nuclear industries. The superior properties of superalloys such as; the high-temperature strength, strain-hardening capacity, poor thermal conductivity and high chemical affinity hinder their machinability and therefore they are known as difficult-to-machine materials. Little studies were done on the machinability of Hastelloy-C276 particularly in term of surface integrity,therefore, this thesis aims to investigate surface integrity and tool wear in groove milling of Hastelloy-C276 using coated carbide end mills coated using different cutting parameters and conditions in the speed range of 24 m/min to 120 m/min. Two aspects of surface integrity were concerned; the arithmetic roughness and the micro-defects. Focusvariation microscope and scanning electron microscope (SEM) with the aid of energy dispersive x-ray spectroscopy (EDX) were used to measure the arithmetic roughness and the micro-defects of the machined surfaces respectively. Cutting speed of 50 m/min and below combined with the minimum feed and non-shallow depth of cut produced superior surface finish with average roughness below 50 nm. The dominant surface defects at low cutting speed were side flow, micro-chips re-deposition and long grooves. At cutting speed of 70 m/min and higher, cracks appeared on ploughed layers on the surface and these cracks are created by the brittle fracture due to the high strain-rate. Other surface defects at high cutting speed were smears, debris and side flow. The increase in surface defects at high cutting speed resulted in increase in surface roughness beyond 100 nm. Surface cavitation appeared at most of the runs and was probably caused by the breakage of the nucleated carbide phases. Tool-workpiece friction in dry machining resulted in large surface craters and large ploughing in addition to severe plastic flow, overlaps and voids created by the thermally induced deformation. Built-up edges formation on the tool faces can be avoided by increasing the cutting speed to 70m/min in wet machining for better chip disposal and only to 50m/min in dry machining since the high oxidation reduces chips adherence tendency. The high oxidation promoted in dry machining resulted in less chips adhesion on groove’s edges due to the poor adhesive capacity of the oxide compounds.